Cytogenetic analysis of a granulocytic sarcoma in a patient without systemic leukaemia. Issue 1 (January 1991) - Adam, L R; Angus, B; Carey, P; Davison, E V
Abstract : Granulocytic sarcoma is a rare complication of leukaemia. Occasionally it presents before the development of systemic leukaemia when diagnosis may be difficult. A case of granulocytic sarcoma occurring in a patient with no overt evidence of leukaemia, but in whom cytogenetic analysis of the bone marrow showed a clonal t(12;13) translocation, is reported. Cytogenetic analysis of tissues in this disease may indicate evidence of systemic disease before overt morphological changes.